Penegakan Hukum terhadap Pelaku Pembuat Dapat Diaksesnya Website Bermuatan Asusila dan Pornografi Anak - Fahmi Aliffio Yudhistira; Hervina Puspitosari (CV Rewang Rencang, 2025)
Law enforcement against perpetrators who create websites containing obscene content and child pornography has become a major challenge in the digital era. The ease of internet access is exploited to spread illegal content that damages morality and threatens children, with 108,508 complaints reported to Komdigi throughout 2024. This research aims to analyze the implementation and obstacles of law enforcement in the East Java Regional Police, covering the effectiveness of enforcement and strategies to overcome barriers such as limited human resources, inadequate facilities, and the complexity of criminal methods. Although law enforcement has been carried out in accordance with existing regulations, it remains largely repressive. Therefore, preventive measures are needed through regulatory updates, enhanced digital forensic capacity, public education, and international cooperation.